Vitamin D level is associated with mortality predictors in ventilator-associated pneumonia caused by Acinetobacter baumannii - BİLGİLİ, BELİZ; YAVUZ, DİLEK; CİNEL, İSMAİL HAKKI (J INFECTION DEVELOPING COUNTRIES, 2016)
Introduction: Vitamin D plays a role in host defense and is known to be associated with mortality in patients in the intensive care unit (ICU). We aimed to evaluate the relationships between vitamin D levels and predictors of mortality in patients with ventilator-associated pneumonia (VAP) caused by extensively drug-resistant Acinetobacter baumanii (XDR A. baumanii). Methodology: A retrospective single-center study was conducted in an 18-bed adult ICU of a teaching hospital, including all patients with VAP due to XDR A. baumanii. Levels of 25(OH) D, procalcitonin (PCT), C-reactive protein (CRP), n-terminal pro-BNP (NT-proBNP), as well as clinical scores (Sequential Organ Failure Assessment [SOFA], Acute Physiology And Chronic Health Evaluation [APACHE II], Clinical Pulmonary Infection Score [CPIS) were recorded. Results: Forty-for patients were studied over six months. All patients had vitamin D deficiency. The 28-day mortality in patients with 25(OH) D levels <= 10 ng/mL was higher than in patients with 25(OH) D > 10ng/mL (p = 0.001). The fourth-and seventh-day SOFA scores (p=0.04 and p=0.001) and first-and fourth-day procalcitonin levels (p = 0.03 and p = 0.004) were higher in patients with 25(OH) D levels <= 10 ng/mL. The clinical scores (SOFA, CPIS, and CEPPIS) and biomarkers (NT-proBNP, PCT) were negatively correlated with 25(OH) D levels in all study groups. Conclusions: Severe vitamin D deficiency was associated with adverse outcome in VAP due to XDR A. baumanii. Vitamin D levels may be a prognostic predictor of VAP. It is also important to evaluate the effect of rapid vitamin D replacement on mortality.
Keywords: vitamin D deficiency; nutrition; ventilator-associated pneumonia; infection; Acinetobacter baumanii; mortality; INTENSIVE-CARE-UNIT; BRAIN NATRIURETIC PEPTIDE; SERUM 25-HYDROXYVITAMIN D; D DEFICIENCY; PROCALCITONIN KINETICS; ACQUIRED PNEUMONIA; SOFA SCORE; INFECTIONS; SEPSIS; PROGNOSIS